Caracterización tecnológica y geomecánica de la formación Huaylillas para fines de uso ornamental en la ciudad de Tacna - Villanueva Arotinco, Juan Diego (2023)
The study area focuses on the Huaylilllas formation located around the city of Tacna, where no zones with potential ornamental use have been identified. A geological-geomorphological and geomechanical mapping was carried out with the aim of providing a technological and geomechanical characterization. Twenty-two geomechanical stations were conducted to obtain a characterization, revealing that the Lower Huaylillas member is poor rock and the upper member is fair to good rock. As it approaches the Millo Formation or the contact with the Lower Huaylillas, the rock's RMR quality decreases. The physical and mechanical properties of 20 samples were determined, yielding the following values: porosity (1.6-32.4%), dry density (1.5-2.3 g/cm3), absorption (0.7-20.4%), specific weight (2.0-2.5 g/cm3), and uniaxial compressive strength (7.98-91.45 MPa). Consolidated tuff with vitroclastolithic lithology and Vitrophydic, Eutaxitic, and Perlitic texture of rhyolitic to trachytic composition was identified. This thesis concludes that the lower member is of poor quality and the upper member of the Fm. Huaylillas is of better quality considering the halo of alteration (15 to 20 m.) of the contacts of the Fm. Millo and the Fm. Huaylillas Inferior, 02 zones are located as quarries located in the Caramolle ravine and in the ravine near Km 17 of the Tarata highway. Keywords: Tuffs, Huaylillas, Characterization, physical-mechanical properties